Cloning and Functional Characterization of Three Odorant Receptors From the Chinese Citrus fly Bactrocera minax (Diptera: Tephritidae) - Liu, Yipeng; Cui, Zhongyi; Wang, Guirong; Zhou, Qiong; Liu, Yang (Frontiers in Physiology, 2020)
Insect olfactory sensing is crucial for finding food, mating, and oviposition preference. Odorant receptors (ORs) play a central role in the transmission of odorant signals into the environment by the peripheral olfactory system. Therefore, the identification and research of ORs is essential to better understand olfactory mechanisms in insects. OR studies on Diptera insects are primarily performed on Drosophila and mosquitoes, but few studies have been reported in Tephritidae. In this study, we examined three candidate ORs (BminOR3, BminOR12, and BminOR16) from Bactrocera minax. Our analysis of tissue expression revealed that the three BminORs were expressed in the antennae, with no difference between the male and female. In in vitro heterologous expression system of Xenopus oocytes. BminOR3/BminOrco responded strongly to 1-octen-3-ol, BminOR12/BminOrco responded to eight compounds (methyl salicylate, benzaldehyde, (Z)-3-hexenyl acetate, butyl acrylate, butyl propionate, 1-octanol, (S)-(+)-carvone and benzyl alcohol), and BminOR16/BminOrco slightly responded to undecanol. Our results concluded that BminOR3, BimOR12, and BminOR16 could play an important role in host-finding and oviposition positioning in B. minax.